2022
DOI: 10.1186/s13287-022-02858-4
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell homing to improve therapeutic efficacy in liver disease

Abstract: Mesenchymal stem cell (MSC) transplantation, as an alternative strategy to orthotopic liver transplantation, has been evaluated for treating end-stage liver disease. Although the therapeutic mechanism of MSC transplantation remains unclear, accumulating evidence has demonstrated that MSCs can regenerate tissues and self-renew to repair the liver through differentiation into hepatocyte-like cells, immune regulation, and anti-fibrotic mechanisms. Multiple clinical trials have confirmed that MSC transplantation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 136 publications
(135 reference statements)
0
20
0
Order By: Relevance
“…These results suggested that an optimal number of seed cells under a specific extent of BMP9 stimulation is enough to repair critical-sized bone defects. In MSC therapy, the seed cell sources and sub-optimal doses usually exhibit inconsistent outcomes in distinct clinical trials [ 65 ]. Meanwhile, MSC treatment is costly, and the greater the demand for seed cells, the higher the price.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that an optimal number of seed cells under a specific extent of BMP9 stimulation is enough to repair critical-sized bone defects. In MSC therapy, the seed cell sources and sub-optimal doses usually exhibit inconsistent outcomes in distinct clinical trials [ 65 ]. Meanwhile, MSC treatment is costly, and the greater the demand for seed cells, the higher the price.…”
Section: Discussionmentioning
confidence: 99%
“…Although beta cells can be derived from pluripotent stem cells, the key question that remains is, under what conditions do bone marrow-derived, beta-like cells migrate to the pancreatic islet in adult animals? It is now generally accepted that stem cells will migrate to sites of injury through stem cell homing [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several MMPs, such as MMP-2 and MT1- MMP, are also indispensable for tissue homing and tissue regeneration of MSCs. Tissue regeneration has been found after MSCs arrive at inflamed tissue ( 108 ). It is well accepted that MSCs contribute to tissue repair, mainly due to their ability to stimulate local tissue proliferation and survival by secreting proteolytic enzymes and angiogenic factors, while inhibiting tissue apoptosis and fibrosis ( 109 ).…”
Section: Mechanisms Of Mscs-based Therapy Of Ibdsmentioning
confidence: 99%